Developing children's character through music a case for philosophy of education - Schnitzlein, Bethel Diokno (2006)
By using the framework of music through a specifically designed intervention, Music is Fun, this study sought to affect significant changes in the character skills and traits in pupils in the level or degree of focus and concentration, participation and cooperation, and confidence and courage among fifth grade elementary public school children. Qualitatively, the findings support the statistical report but provide more depth. When asked to name the top three traits they gained from Music is Fun, the students listed the ff: to have hope in life, to have courage and to have patience. Implications for philosophy of education were deduced.
"October 2006."
Thesis (Ph.D. Education : History and Philosophy of Education)--University of the Philippines, Diliman.
Keywords: Music -- Instruction and study -- Philippines -- Quezon City -- Juvenile; Personality development -- Philippines -- Quezon City; Fifth grade (Education) -- Philippines -- Quezon City